The impact of microfinance services on household economic well-being with the moderating role of microfinance institutions' credibility - Abdullah, W Muhammad Zainuddin B Wan; Zainudin, Wan Nur Rahini Aznie Bt; Zia-ul-haq, Hafiz Muhammad (Asian Development Policy Review, 2024)
The main purpose of this study is to investigate the impact of microfinance services on the economic well-being of clients in Malaysia and to explore how the credibility of microfinance institutions moderates the relationship between microfinance services and economic well-being. The data was collected from clients of Amanah Ikhtiar Malaysia, the largest microfinance organization catering to low-income households in Malaysia for this study. The research applied measurement and structural models to analyze the data and test the formulated research hypotheses comprehensively employing structural equation modeling. The analysis results demonstrated a significant and positive impact of financial and non-financial microfinance services on the economic well-being of clients. Furthermore, the findings also revealed that the credibility of microfinance institutions plays a crucial role in augmenting the effectiveness of financial services in fostering economic success. In essence, this research suggests that the credibility of microfinance institutions strengthens the impact of financial interventions aimed at improving clients' economic status. These outcomes have significant implications for the design and implementation of microfinance programs in Malaysia emphasizing the importance of financial and non-financial services and the credibility of the institutions delivering them in positively influencing clients’ economic well-being.